OPTIMIZING POSTHARVEST HANDLING PROTOCOLS FOR CUT Helianthus annuus L. - A NOVEL SPECIALTY CUT FLOWER - Hifza Safdar; Iftikhar Ahmad; John M. Dole; Hina Safdar; Ayesha Jabeen (Journal of Animal and Plant Sciences, 2026)
Research was conducted to assess the response of Helianthus annuus L. (sunflower) to various postharvest handling procedures for optimizing suitable protocols and ensuring the longest possible vase life. Experiments were conducted to optimize the harvest stage, harvest time, handling procedures, vase water quality, pulsing preservatives and vase preservatives.For harvest stage, partially opened flowers had the longest vase life (7.5 d), followed by stems harvested at closed bud stage (6.5 d). For harvest time, stems harvested in evening had longest vase life (7.6 d). For handling procedure, longest vase life (7.1 d) was recorded in wet-wet (continuously) hydrated throughout handling, succeeded by dry-wet handled stems (5.4 d). For water quality, 5% sucrose with distilled water had longest vase life (8.2 d). For storage methods and durations, stems that were not stored had the longest vase life, while the stems that were stored had the shorter vase life. For pulsing solutions, stems pulsed with Chrysal Clear Universal flower food had the longest vase life (11.6 d). In vase preservatives, Floralife flower food demonstrated the most prolonged vase longevity (12.8 d), closely succeeded by Chrysal Clear Universal flower food (12.6 d). In summary, for sunflower postharvest longevity, stems should be harvested in the evening at partially opened stage and should be placed in water immediately. Moreover, stems may be pulsed with 5% sucrose and for vase solutions, stems should be placed in Commercial preservatives, such as Floralife flower food or Chrysal Clear Universal flower food or homemade solutions, such as lemon/lime soda + distilled water (50:50) for longest vase life.
Keywords: Commercial preservatives; electrolyte leakage; storage; sunflower; vase life